Tracheobronchial amyloidosis following COVID‐19 infection - Chathurangi Angammana; Sameera Gamlath; Ravini Karunathilake; Shehan Silva (Respirology Case Reports)
Abstract Deposition of amyloid proteins in extracellular space can occur due to uncontrolled inflammatory processes. Tracheobronchial amyloidosis (TBA) is a rare form of such disease. A 68‐year‐old woman was evaluated for chronic cough following a COVID‐19 infection. Although post‐viral sequelae were suspected, further investigation revealed TBA. This condition involves amyloid deposits within the airways. The temporal association with COVID‐19 raises a potential etiological link, suggesting viral‐induced inflammatory or immune‐mediated processes may play a role. This case underlines the need to consider rare etiologies like TBA in patients with unresolved respiratory symptoms post‐COVID‐19.